ANALISIS TINGKAT DEPRESI PADA SISWI SMK MUHAMMADIYAH KABUPATEN WONOGIRI - Nurtanti, Susana (Jurnal AKPER GSH, 2021)
Background: The problems of depression have become health challenges in almost all over the world, including in Indonesia. Objective: The purpose of this study was to determine the prevalence level of depression in adolescent at SMK Muhammadiyah Baturetno, Wonogiri Regency, Indonesia. Method: The design of this study was a descriptive quantitative study with a cross-sectional approach. The instrument in this study used a questionnaire about DASS42. Results: Most of the respondents of the study the prevalence of depression was 35 (12.1%), anxiety was 115 (39.8%) and stress was 139 (48.1%). Conclusion: From the results of the study, the prevalence of depression was 35 (12.1%), anxiety was 115 (39.8%) and stress was 139 (48.1%).